2015
DOI: 10.1002/cncr.29303
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of gene methylation in surgical margin imprints with locoregional recurrence in head and neck squamous cell carcinoma

Abstract: Background Securing negative surgical margins is a critical goal for head and neck surgery. Local recurrence occurs even in some cases with histologically negative surgical margins. Minimal residual tumor cells may lead to locoregional recurrence despite clear histologic margins reported at the time of resection of head and neck squamous cell carcinoma (HNSCC). In order to identify subclinical residual disease, we analyzed deep margin imprint samples collected on one layer nitrocellulose sheets. Methods Bisu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 38 publications
1
32
0
3
Order By: Relevance
“…We hypothesized that margin imprints might assess the molecular margin status more accurately than collecting tissue samples from margins in the standard manner. We confirmed this hypothesis in a recent study(10) showing that the methylation marker combination of HOXA9 and EDNRB was a more powerful predictor of outcome than conventional tumor factors (TNM stage, differentiation). Locoregional recurrence free survival (LRFS) was more highly associated with molecular margin status than was recurrence free survival or overall survival.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…We hypothesized that margin imprints might assess the molecular margin status more accurately than collecting tissue samples from margins in the standard manner. We confirmed this hypothesis in a recent study(10) showing that the methylation marker combination of HOXA9 and EDNRB was a more powerful predictor of outcome than conventional tumor factors (TNM stage, differentiation). Locoregional recurrence free survival (LRFS) was more highly associated with molecular margin status than was recurrence free survival or overall survival.…”
Section: Introductionsupporting
confidence: 88%
“…QMSP is a well-established technique for detecting low levels of tumor DNA in various body fluids such as saliva(27, 28) and urine(29). Practically, the adaptation of this approach to HNSCC surgical margin analysis using imprint methods also has been shown to have acceptable quality in our recent study(10). In order to realize general clinical adoption of imprint molecular assessment, several refinements are needed.…”
Section: Discussionmentioning
confidence: 84%
“…53 Moreover, epigenetic events, such as aberrant promoter gene hypermethylation, are often observed not only in tumor tissue, but also in surgical margins. 39,54,55 Abnormal DNA methylation patterns in promoter regions can inactivate genes and facilitate tumor formation and progression. 56 Environmental factors like exposure to alcohol and cigarettes can influence aberrant methylation patterns, too.…”
Section: Dapk1mentioning
confidence: 99%
“…Given these barriers of HPV DNA‐based population screening for HPV‐positive OPSCC, it is attractive to define other measurable DNA alterations characteristic of HPV‐positive OPSCC. Extensive number of studies have demonstrated that abnormal epigenetic regulation is closely related to tumorigenesis . The dominant paradigm includes that methylation of CpG island promoter results in transcriptional repression of tumor suppressor gene.…”
Section: Introductionmentioning
confidence: 99%